2021
DOI: 10.1080/15295192.2021.1908090
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mothers’ and Fathers’ Positive Parenting for Toddlers’ and Preschoolers’ Social-Emotional Adjustment

Abstract: Parental support, stimulation, positive discipline, and structure are all important for social-emotional adjustment of toddlers and preschoolers. However, less is known about the relative importance of these positive parenting practices. The current crosssectional study examines the associations between positive parenting practices and child social-emotional difficulties in relation to child age and parental gender. Design. 446 Dutch families (446 mothers, M age = 33.51 years; 446 fathers, M age = 35.63 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
4
18
0
3
Order By: Relevance
“…More surprisingly, mothers particularly those who have no better educational background experienced barriers in helping their children's studies like they have difficulties in operating technology and others. Further, this study reflects that the need of involvement of parents not only mother but also father in encouraging the children's social and emotional adjustment (Okorn et al, 2021). Finally, this study pinpoints that teachers need to reconsider the children's ability in learning independently so that the parents will feel satisfied (Lau et al, 2021).…”
Section: Lack Of Training and Supportmentioning
confidence: 63%
See 1 more Smart Citation
“…More surprisingly, mothers particularly those who have no better educational background experienced barriers in helping their children's studies like they have difficulties in operating technology and others. Further, this study reflects that the need of involvement of parents not only mother but also father in encouraging the children's social and emotional adjustment (Okorn et al, 2021). Finally, this study pinpoints that teachers need to reconsider the children's ability in learning independently so that the parents will feel satisfied (Lau et al, 2021).…”
Section: Lack Of Training and Supportmentioning
confidence: 63%
“…Furthermore, in online classes, the involvement of parents particularly mothers in preschool-aged children's education has played a great role. It has shown that positive parenting is crucial to enhance children's emotional and social growth (Okorn et al, 2021). Therefore, parents need to invest in their children to be ready for school in the early years.…”
Section: A Introductionmentioning
confidence: 99%
“…This technical procedure was created by Baranzini [ 20 ], which facilitates the compression of several imputed data frame outputs into a single pooled data frame. This method has also been used by other researchers [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Children with an incarcerated mother lived with their fathers roughly a third of the time while most lived with a grandparent or another relative. If mothers are not able to meet the child's needs properly, their parenting may be less effective in preventing a child from experiencing social-emotional problems (Okorn et al, 2021). An assessment by Dworsky et al (2020) highlighted four key challenges to building relationships between incarcerated mothers and their children namely: the prison was neither staffed nor designed to support childfriendly visitation, women had limited opportunities to call their children or other family members, the only state-funded program that provided transportation for children to visit their mothers in prison had been eliminated, and enrollment in the prison nursery had plummeted despite a zero percent recidivism rate among participants.…”
Section: Experiences Of Children With Incarcerated Mothersmentioning
confidence: 99%